Advances in the bioregulation of mesenchymal stem cells by low-level laser therapy during bone formation: a narrative review - Wang, Yan Pei; Mohamad Arif Awang Nawi,; Norma Ab Rahman,
This article reviews the progress of research on the modulation of the biological effects of low-level laser therapy (LLLT) on Mesenchymal stem cells (MSC) and the influence of the basic LLLT parameters and irradiation scenarios. A thorough search of the literature in the PubMed, Web of Science and Embase databases, including articles published in peer-reviewed journals, was conducted to collect relevant information on LLLT and MSCs. A comprehensive search of PubMed, Web of Science, and Embase databases was performed using the keywords “Low level laser,” “mesenchymal stem cells,” “ cell proliferation,” and “osteogenic differentiation.” The search was limited to studies published in English between 2009 and 2022, including in vitro and in vivo studies. LLLT has the potential to promote MSC proliferation and osteogenic differentiation, with significant applications in bone tissue engineering. Factors that influence the biological effects of LLLT on MSC include cell type, culture medium, duration of irradiation, the frequency of laser irradiation, irradiation spot size, and type of light flux distribution. The limitations of this review include heterogeneous experimental conditions and the inability to design experiments that consider all influencing factors simultaneously.